Dental Anomalies as Late Adverse Effect among Young Children Treated for Cancer - Proc, Patrycja; Szczepańska, Joanna; Skiba, Adam; Zubowska, Małgorzata; Fendler, Wojciech; Młynarski, Wojciech (Cancer research and treatment, 2016)
The aim of this study was to compare the incidence of dental complications in childhood cancer survivors with that of healthy control subjects, and to determine the possible influence of various factors associated with patient and treatment. Sixty-one panoramic radiographs of the dentition of cancer survivors were compared with 521 radiographs of healthy patients at a similar age, between 5 and 18 years. The mean period from termination of therapy was 4.9 years (58.9 ± 34.3 months), and 51 children (83.60%) were under age 5 when therapy began. Dental anomalies were found in 38 cancer survivors (62.29%) and 69 control subjects (13.24%) (p < 0.001). Agenesis of teeth was found in 19 cancer patients (31.14%) and in 48 control subjects (9.21%). Microdontic teeth were found in 22 cancer survivors (36.06%) and 15 control subjects (2.87%) (p < 0.001), whereas teeth with short roots were found in seven cancer patients (11.47%) and 15 control subjects (2.87%) (p < 0.01). Dental anomalies in cancer patients were more common in some tooth groups and were not observed in others. The frequency of dental anomalies did not show correlation with age at the beginning or termination or time of therapy. Children under the age of 5 are in a high risk group for dental complications after anticancer treatment. Rudimentary chemotherapy has a considerable impact on the occurrence of dental anomalies.